PENGARUH ASOSIASI MEREK, KESETIAAN MEREK, KESADARAN MEREK, DAN CITRA MEREK TERHADAP EKUITAS MEREK PADA PENGGUNA SMARTPHONE OPPO - Yenny Lego; Hannes Widjaya (Jurnal Bina Manajemen, 2021)
The very high growth of smartphone users in Indonesia makes companies that issue smartphone products have to try to be the best among other smartphone companies. Currently, OPPO is in second place in the smartphone market share in Indonesia in the second quarter of 2019. The aim of this study is to determine brand association, brand loyalty, brand awareness and brand image have an influence on brand equity. The sampling technique was carried out by purposive sampling. The questionnaire was distributed to 150 respondents in Karawaci Tangerang who were OPPO smartphone users. The results of this study indicate that there is an effect of brand association on brand equity, meanwhile, brand loyalty, brand awareness, and brand image have no influence on brand equity.